Hubungan Peran Tim Pencegahan dan Pengendalian Infeksi dengan Kepatuhan Perawat dalam Melakukan Hand Hygiene di Ruang Rawat Inap RS Harapan Bunda - Nurul Fitrah Fauziah; Solehudin Solehudin; Inas Syabanasyah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
HAI's is an infection that patients get when using health facilities or undergoing treatment in hospitals that when they enter the incubation period. Hand hygiene is a term used to wash hands, there are two ways that can be used in washing hands, namely using alcohol-based hand sanitizers and soap. The type of research used is correlation analysis with a cross sectional research design. The sampling technique uses total sampling. The data collection technique used a questionnaire of 22 questions and an observation sheet of five moments and six steps of hand hygiene. The research sample was 70 respondents. Therefore, it was concluded that there was a significant relationship between the role of the Infection Prevention and Control Team and nurses' compliance in carrying out hand hygiene in the inpatient room of Harapan Bunda Hospital.